THE ACTION OF FOOTBALL SUPPORTERS IN SUSTAINING SPORTS STADIUM - Anshari, Faridhian (Gunahumas, 2018)
ABSTRACT The sports stadium is an important element in organizing a football match. From a number of negative cases related to the behavior of football supporters in Indonesia, the story of the destruction of stadium facilities by the supporter is quite often become the headline in various media. One of the major  events that occurred was the destruction of the Gelora Bung Karno National Stadium (GBK) facilities in the 2018 Presidential Cup final by some individuals who were thought to be supporters of the Persija Jakarta club. The biggest problem is, the stadium facilities are still in trial after renovation and  will be prepared for the 2018 ASIAN Games. Encouraged by the guilty pleasure, Jakmania as Persija  Jakarta's Supporters took an independent initiative by raising the #JagaGBK movement without any interference with the club's managerial. The purpose of this campaign is to maintain the surrounding  environment and sports facilities inside the GBK stadium. This grassroots movement involves all  Jakmania who are estimated around 45,000 people from 66 Regional Coordinators. The purpose of  this study is to understand the use of campaign techniques carried out by Jakmania in performing the  #JagaGBK campaign. This study used a qualitative approach with data collection techniques through  in-depth interviews with three resource persons: the main chairperson of Jakmania, the Jakmania  board of trustees, and the Head of branch Jakmania East Jakarta. This research resulted in findings  related to strategies in assembling member participation, similarity goal associations, efforts to unite  (integrative), giving rewards, delivering messages, gaining empathy, and giving coercion to members  who are not involved in running #JagaGBK campaigns. This research is expected to find a  formulation that can be an inspiration for other campaigns which held by the football supporters, specially regarding environmental preservation and the sports facilities.Keywords: Supporters, Football, Campaign #JagaGBK, Jakmania, and Persija Jakarta.